2016
DOI: 10.1007/978-3-319-42044-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Non-dividing Cell Virtosomes Affect In Vitro and In Vivo Tumour Cell Replication

Abstract: In vitro studies of partially purified virtosomes from rat liver showed inhibition of cell multiplication in four normal and two tumour cell lines. In vivo, the liver virtosomes slowed tumour growth and limited metastases in rats bearing DHD/K12-PROb cell initiated tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The production of exosomes has been shown to be markedly elevated in cancer [ 98 ], which can affect recipient cells in a variety of ways, e.g., development of acquired resistance to chemotherapeutic agents [ 99 ]. In contrast to the above observations, one in vitro study suggests that the lateral transfer of cfDNA derived from healthy cells can potentially halt the proliferation of cancer cells [ 100 ]. However, this requires further experimental verification.…”
Section: Roles Of Cfdna In the Pathology Of Cancermentioning
confidence: 99%
“…The production of exosomes has been shown to be markedly elevated in cancer [ 98 ], which can affect recipient cells in a variety of ways, e.g., development of acquired resistance to chemotherapeutic agents [ 99 ]. In contrast to the above observations, one in vitro study suggests that the lateral transfer of cfDNA derived from healthy cells can potentially halt the proliferation of cancer cells [ 100 ]. However, this requires further experimental verification.…”
Section: Roles Of Cfdna In the Pathology Of Cancermentioning
confidence: 99%
“…() and Garcia‐Arranz et al . (), who showed that virtosomes from non‐dividing cell populations can reduce tumour size in tumour‐bearing BDIX rats. Due to the presence of proteins in virtosomes, histological analysis of a range of tissues was performed and it was confirmed that proteins from the virtosomes were not responsible for the anti‐tumour effects.…”
Section: Sources Of Circulating Cfdnamentioning
confidence: 99%
“…A similar form of homeostasis may occur between populations of cells in order to equilibrate or manage genetic and/or epigenetic changes throughout tissues, organs and/or the body (Aucamp et al, ). The fact that ( i ) virtosomes have been found readily to enter other cells in vitro and in vivo and modify the biology of the recipient cells (Adams, Diaz & Gahan, ; García‐Olmo, Ruiz‐Piqueras & García‐Olmo, ; García‐Olmo et al, , ; Garcia‐Arranz et al, ) and ( ii ) cfDNA has been found to contain information/mutations similar to those of parental cells and can transfer this information between cells, e.g. chemoresistance (Chen et al, ), indicates that the messaging role of cfDNA in virtosomes and vesicles may indeed have homeostatic properties (Fig.…”
Section: Sources Of Circulating Cfdnamentioning
confidence: 99%
“…cfDNA affects many parameters of the organism. Circulating cfDNA can increase oxidative stress, stimulate the synthesis of proinflammatory cytokines, induce sterile inflammation, affect platelet activation, plasmatic coagulation, and fibrinolysis, and activate a large number of signaling pathways [24, 25].…”
Section: Circulating Cell-free Dnamentioning
confidence: 99%